Application Of An Artificial Intelligence Algorithm For Computer-Assisted Cancer Detection - Mr.Athiraja A, Mr.S.Arulraj, Mrs.Megala N , Mr.P.Prasana , Mr. Karl Joseph Samuel, Mrs.J.Jareena Begam (Drugs and Cell Therapies in Hematology, 2021)
The perceptron algorithm has been developed as a tool for detecting cancer. Currently, virtually all techniques for identifying illness are based on micro calcifications (MC's). MC's are calcium reserves that appear as a magnificent spot on a mammography. There are three types of AI calculations: directed learning, unassisted learning, and support learning. The perceptron algorithm is a mammography grouping method that uses an administered arrangement approach to group the MC's current cell and MC's missing cells. In the realm of clinical image preparation, CAD (Computer Aided Detection) for mammography is a research area. The goal of this project is to use the Perceptron method to find the MC's cells in a mammogram.